THE INFLUENCE OF REPRODUCTIVE HEALTH PROMOTION ON INCREASING THE KNOWLEDGE OF SANTRI AT THE ANSHORUSSUNNAH MANTINGAN ISLAMIC BOARDING SCHOOL - Farras Kens Daryngga; Arif Widodo (Professional Health Journal)
Introduction: School is a place to obtain education and knowledge about reproductive health for teenagers. One of the educational models in Indonesia is Islamic boarding schools.